The Influence of Corporate Governance on Company Financial Difficulties with Political Connections as Moderation - Teddy Jurnali; Wulan Angreni (Universitas Internasional Batam, 2024)
This study aims to analyze the influence of corporate governance on corporate financial distress with political connections as a moderation. The research population used is data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) from the 2017-2021 period. Sampling using purposive sampling. Data analysis was performed using panel data regression and using Eviews software. Research shows that board size has a negative effect on financial distress, while family ownership has no significant effect. This research shows that political connections can strengthen the relationship between board size and family ownership of financial distress in companies